Benefit Incidence Analysis of HIV and AIDS treatment policy in Thailand - Pinthong, Pichate (Journal of Public Administration, Public Affairs, and Management, 2021)
Thailand has been one of the leading developing countries in providing HIV and AIDS patients access to HIV therapy free of cost treatment. The objective of this research paper was to analyze the benefit incidence of HIV and AIDS treatment policies in Thailand. The quantitative research methodology was used. Data were collected from people receiving HIV antiretroviral therapy in 13 service areas of the National Health Security Office (NHSO) covering all regions of Thailand. The samples were 665 people and stratified sampling was used. The findings revealed that the Benefit Incidence Analysis of HIV and AIDS treatment policies in Thailand investigated that people who accessed HIV antiretrovirals were 69 percent higher in income than the poverty line. When classified by their eligibility for medical care, it was found that group 1 (lowest income) and group 2 (low income) or the poor were the majority in accessing to Universal Health-care Coverage Scheme (UHC) (Gold Card) or 30 baht cures all diseases. However, classifying for each group, it was found that group 3 (middle income) received more benefits than all income groups, while the fourth (high income) and the fifth (highest income) was benefited in the Social Security Scheme (SSS) the most. This finding showed that the Social Security Scheme (SSS) benefited more common in non-poor people. As for the recommendations, governments should only impose access to treatment rights for the poor to receive free treatment and expand the social security right system to cover more informal workers, which is the majority of the country's labor force.